Performance of Organic Rankine Cycle in Different Refrigerants for Low Temperature Geothermal using Delphi Program - Prabowo .; Andre G.T.; Ekadewi . (Jurnal Teknik Mesin (Sinta 3), 2010)
A software has been developed in a Windows-based Delphi programming for analyzing the influence of the transport and thermodynamic properties of the refrigerants on the performance of the Organic Rankine Cycle (ORC). Its user-friendly drag and drop icon format and excellent color graphics make it an interactive tool for teaching and the preliminary design of the ORC system. The research was carried out by analyzing the performance of the system components and the overall ORC based on the several working fluids within R22, R123, R134a and RC318. The pressure of evaporator was varied in two steps 7 and 12 bar, while the condenser was kept constant pressure at 1 bar. The turbine inlet temperature was varied in the range 100 0C to 140 0C where the various isentropic efficiency inputs were applied for pump and turbine. By increasing turbine inlet temperature, R22 has the highest turbine work output and cycle efficiency. Contrary, RC318 has the lowest cycle efficiency and decreases trend with enhancing in turbine inlet temperature. RC318 has low latent heat of vaporization thus vaporizes under relatively very low evaporator heat supply.